HUBUNGAN PERSEPSI MAHASISWA TENTANG METODE PENGAJARAN DOSEN DENGAN MOTIVASI BELAJAR PADA MAHASISWA KEPERAWATAN - Lia Dwi Jayanti (Coping: Community of Publishing in Nursing, 2014)
Motivation is the change of person’s energy that is characterized by presence of "feeling" and preceded by the response to the presence of the goal. Learning motivation is encouragement that exists and emerges in student to learn. In order to fulfill the terms of the right quality of learning, there are three aspects that need to be considered, such as students, faculty, and the environment. The quality of lecturers has the strongest relationship with learning motivation compared to intrinsic factors, methods of lectures, and material from college. A method of this research is descriptive correlation with cross-sectional design. The sample is consisted of 75 respondents who met the inclusion criteria and were selected by purposive sampling technique. Data collection was conducted by giving questionnaire to both variables. The results showed that the perception of students about lecturer’s teaching method is the most in medium category as many as 47 respondents (62.7 %) and 55 respondents in high category of learning motivation (73.3 %). This research used Rank Spearman statistic test and is obtained p value 0.000 < 0.05 means H0 is rejected which means there is a relationship between students' perceptions of lecturer’s teaching methods toward learning motivation on Nursing Student in 8th Semester A Program.  The value of r is 0.662 which means there is a strong relationship between students' perceptions of lecturer’s teaching methods toward learning motivation. For further research, the researcher is expected to examine other variables that can affect the learning motivation.